Analysis of risky food consumption behavior among university students - Djannah, Sitti Nur; Handayani, Lina; Ruliyandari, Rochana; Tukiyo, Intan Wahyuni (International Journal of Public Health Science (IJPHS), 2023)
Non-communicable diseases (NCD) and oral disease problems can arise in all age groups, including teenagers. Risky behavior is caused by a poor lifestyle and other factors. This study aimed to determine risky behavior and NCD incidence as well as oral problems in students at the Yogyakarta campus. This can lead NCD and oral problems. This research is quantitative descriptive-analytic research condected in a private university in Yogyakarta. The data was collected through an electronic questionnaire (Google form) and analyzed descriptively. Among the students' risky behaviors, 87.27% consumed excessive sweet food, 87.88% salty food, 82.42% oily food, 80% of seasonings, 57.58% consumed instant noodles, 84.85% consumed too little fruit and vegetables, and 87.27% did not participate in physical activity for 30 minutes. In the last 12 months, there was a high incidence of dental and oral health issues among students without symptoms. It was concluded that the most dominant risk behavior for non- communicable disease correlated with poor diet related to food consumption and lack of physical activity. All students had no symptoms or no doctor's diagnosis, but students experienced oral health problem within 12 months. A healthy diet, regular exercise, and good oral hygiene can reduce the risk of NCDs and dental and oral diseases.